Morbus Dupuytren: Epidemiologie, Diagnose, Therapie, Outcome : CME : zertifizierte Fortbildung - Harbrecht, Andreas; Honigmann, Philipp; Löw, Steffen; Müller, Lars Peter; Unglaub, Frank; Spies, Christian (Die Orthopädie, 2024)
Dupuytren’s contracture is a fibroproliferative systemic disease that cannot be stopped by medication. The overall prevalence is 7-8%. Men are affected 3-4 times more frequently. The cause of the disease is not known. A genetic disposition and thus familial clustering are being discussed. Risk factors for the development of a Dupuytren’s contracture are work-related stress (microtrauma), nicotine and alcohol consumption, epilepsy and diabetes mellitus as well as advanced age. The prognosis is poor in cases with a positive family history, bilateral involvement, age <50 years and male gender. Several treatment options are available. Conservative therapy has no lasting benefit. Minimally invasive procedures include partial needle aponeurectomy or the injection of collagenase. Surgical procedures range from partial aponeurectomy to dermatoaponeurectomy. The recurrence risk of the gold standard treatment of surgery (partial aponeurectomy) is 20.9%.
Online publiziert: 25. September 2024
Gesehen am 20.01.2025